INFγ, TNFα, IL-6 LEVELS IN THE PERIPHERAL BLOOD SERUM IN DIFFERENT CLINICAL COURSES OF NONSPECIFIC VULVOVAGINITIS IN ADOLESCENT GIRLS - Kenzhebekovna, Smailova Lazat; Tursunovna, Bilalova Gulshat; Medeubaeva, Kurmanova Almagul (International Journal of Research -GRANTHAALAYAH, 2017)
The conducted study showed that increased production of anti-inflammatory INFγ cytokine is observed in girls and adolescents with acute nonspecific vulvovaginitis compared to the subacute course of the disease, though no adequately high production of this cytokine is practically observed in both cases. The obtained data indicate the suppression of both the cell and humoral anti-inflammatory immunity. IL-6 is responsible for the specificity and the adequacy of immunological reactions. This fact is connected primarily with the presence of multidirectional pathological changes in the immunity system.